A hexagonal high-performance transformer balun based on TSV technology for W-band application. Issue 1 (1st December 2022) - Wang, Fengjuan; Zhang, Dingxi; Yu, Ningmei; Yang, Yuan
Abstract: Balun has been widely used for microwave circuits for its balance properties. The development of highly integrated RF systems has put forward higher requirements for superior performance and miniaturization of the balun. A compact broadband millimeter wave (MMW) transformer balun based on through silicon via (TSV) technology is proposed in this letter. Compared with the traditional balun, the proposed balun impedance ratio is 4:1, and the use of hexagonal coil winding significantly reduces its area and improves its performance. It is shown that the proposed balun has a magnitude imbalance of 0.64dB and a phase imbalance of 2.5° at 81.5-93GHz. A return loss of greater than 15dB is obtained for the frequency band ranges from 82.1-88.6 GHz. Furthermore, the area of balun is only 0.201×0.29mm 2 (0.2×0.29λg2).